Identification of two missense mutations in a dihydrolipoamide dehydrogenase-deficient patient. - Liu, T C (1993)
The molecular basis of dihydrolipoamide dehydrogenase (E3; dihydrolipoamide:NAD+ oxidoreductase, EC 1.8.1.4) deficiency in an E3-deficient patient was studied. Fibroblasts cultured from the patient contained only approximately 6% of the E3 activity of cells from a normal subject. Western and Northern blot analyses indicated that, compared to control cells, the patient's cells had a reduced amount of protein but normal amounts of E3 mRNA. Direct sequencing of E3 cDNA derived from the patient's RNA as well as each of the subclones of the cDNA revealed that the patient had two substitution mutations in the E3 coding region. One mutation changed a single nucleotide from A to G, resulting in substitution of Glu (GAA) for Lys-37 (AAA). The other point mutation was a nucleotide change from C to T, resulting in the substitution of Leu (CTG) for Pro-453 (CCG). These mutations appear to be significant in that they alter the active site and possibly the binding of FAD.